Walking and Dry Season Stresses Modulates the Physiological, Heamatological and Biochemical Profiles of Indigenous Local Goats in Andaman and Nicobar Islands - Perumal, P.; De, A. K.; Bhattacharya, D.; Sunder, J.; Bhowmick, S.; Kundu, A.; Muniswamy, K. (International Journal of Bio-resource and Stress Management, 2020)
A study was designed to assess the walking stress and dry seasonal effect on physiological, heamatological and biochemical profiles in indigenous local goat breeds of Andaman and Nicobar Islands (ANI). Twelve bucks of adult age of 3 to 4 yr of age with good body condition (score 5-6) were selected and divided into two groups, viz. group-I: control (n=6, not exposed to stress) and group-II: treatment (n=6, exposed to walking and dry season stress). In treatment group, animals were walked upto10 km to and fro from goat farm in undulated area without allowing grazing. Whereas control animals were placed in separate adjacent goat shed covered with asbestos roof and surrounded by natural trees. Walking time was from 0700 to 1200 h. Experiment was conducted during dry season (November to February). These animals were restrained and physiological parameters were measured immediately after stressful walk in dry season. Simultaneously, blood samples were collected for the heamatological study and antioxidant attributes. The result of the present study revealed that the physiological, heamatological profiles as well as the malondialdehyde concentration were significantly (p<0.05) increased and antioxidant profiles were significantly (p<0.05) decreased in the treatment stressed goats than in unstressed control group. From the study, it was concluded that the process of walking in dry season has induced walking and thermal stress that has significantly (p<0.05) affected the performance of indigenous local goat breeds of ANI.